Statistical Analysis on Preliminary Breakdown Pulses of Positive Cloud-to-Ground Lightning in Malaysia - Chin-Leong Wooi; Zulkurnain Abdul-Malek; Noor Azlinda Ahmad; Mehrdad Mokhtari; Behnam Salimi (Institute of Advanced Engineering and Science, 2016)
This aim of this paper is to study the preliminary breakdown pulses (PBP) of positive cloud-to-ground (+CG) lightning flashes in Malaysia. There is a difference in PBP characteristics when a comparison is made between positive and negative flashes. To the best of the authors’ knowledge, this is the first time the PBP characteristics preceding positive lightning in Malaysia are reported. This study was carried out in Johor Bahru, Malaysia using a broadband antenna system during a monsoon period (Oct-Dec, 2012). It is found that the PBP for +CG lightning is much more complicated compared to the positive cloud-to-ground (–CG) lightning since only negative PBP trains are usually present in the –CG lightning. Out of 21 analyzed positive flashes, four types of PBP trains were identified according to their initial polarities. These are negative PBP (20%), positive PBP (15%), PBP with polarity reversal (10%), and PBP with irregular polarity (15%). The balance 40% of flashes are without any PBP. The effect of geographical region may also cause the observed differences in the cloud discharge processes including the types of PBP. More studies are needed to determine the relationship between the return stroke and PBP.